1985
DOI: 10.1007/bf02917455
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and copper in hyperlipoproteinemia

Abstract: Starting from experimental observations demonstrating that a high ratio of zinc to copper led to hypercholesterolemia in rats, serum Zn and Cu levels were measured by atomic absorption spectrophotometry in 65 normolipemic controls and in 100 subjects with various types of hyperlipoproteinemia (HLP). Serum Zn levels did not significantly differ from control values in any type of HLP. However, hyperlipoproteinemic patients with obvious clinical atherosclerosis displayed significantly lower serum-Zn concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Many studies from animal models to human clinical data reported that plasma Cu levels are significantly elevated along with hypercholesterolemia in atherosclerotic subjects [ 140 , 141 ]. Two cross-sectional clinical studies with apparently healthy subjects showed that serum Cu was inversely associated with low-density lipoprotein cholesterol (LDL-C), suggesting that a higher or adequate serum Cu level is linked to a better lipid metabolic state [ 210 ].…”
Section: Disturbance Of Cu Homeostasis In Atherosclerosismentioning
confidence: 99%
“…Many studies from animal models to human clinical data reported that plasma Cu levels are significantly elevated along with hypercholesterolemia in atherosclerotic subjects [ 140 , 141 ]. Two cross-sectional clinical studies with apparently healthy subjects showed that serum Cu was inversely associated with low-density lipoprotein cholesterol (LDL-C), suggesting that a higher or adequate serum Cu level is linked to a better lipid metabolic state [ 210 ].…”
Section: Disturbance Of Cu Homeostasis In Atherosclerosismentioning
confidence: 99%
“…14 Many studies from animal models to human clinical data found that plasma copper levels are significantly elevated along with hypercholesterolemia in atherosclerotic subjects. 15,16 Copper ions catalyze oxidative modification of LDL in vitro 17,18 and there are also reports on copper participation in the oxidation of LDL in vivo. 19,20 The increase in plasma copper from high-cholesterol feeding would promote oxidative modification of LDL, thus promoting atherosclerosis.…”
Section: Impact Statementmentioning
confidence: 99%